2019
DOI: 10.15666/aeer/1702_35673574
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Glycoalkaloids in Potato Under the Influence of Biostimulators

Abstract: control variant. In the biostimulators group there were products containing functional elements, eg titanium, products based on algae extracts, and products containing amino acids. The lowest concentration of glycoalkaloids in leaves and tubers of edible potato was found in the Jelly variety -251 mg•kg -1 on average in leaves, and -80.5 mg•kg -1 in tubers, while the largest in the Tajfun varietyon average in leaves 370 mg•kg -1 , in tubers 110 mg•kg -1 . Under the influence of all bioregulators, there was a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…Whereas, the lowest TGA was determined in the growing season of 2019 with the lowest rainfall. A similar response associated with the weather conditions was reported by other researchers (Żołnowski 2001, Gugała et al 2016, Mystkowska 2019.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Whereas, the lowest TGA was determined in the growing season of 2019 with the lowest rainfall. A similar response associated with the weather conditions was reported by other researchers (Żołnowski 2001, Gugała et al 2016, Mystkowska 2019.…”
Section: Resultssupporting
confidence: 89%
“…It has been shown that the highest concentration of glycoalkaloids, on average 94.17 mg/kg of fresh matter, occurred in 2020, when rainfall was the highest, and the lowest in 2019, characterised by low rainfall. Similar results were described by Zarzecka et al (2013), Hamouz et al (2014), Mystkowska (2019), Wszelaczyńska et al (2020). Żołnowski (2001) found that high levels of glycoalkaloids occur in plants when metabolism is very intense.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Numerous factors affect the formation of glycoalkaloids in potatoes: environmental and growing conditions, maturity during harvesting time, temperature during growth, and extent of sprouting, as well as any mechanical damage such as bruising, cutting, wounding, and slicing while handling. Postharvest storage conditions, especially the wavelength, duration, and intensity of light during storage can also play a crucial role on the glycoalkaloid content of potatoes, while other environmental conditions during packaging, transportation, and marketing can have an effect on it as well [ 48 , 49 ]. A previous study [ 14 ] found no statistically significant changes to the glycoalkaloid content of whole potatoes after HPP treatment.…”
Section: Resultsmentioning
confidence: 99%
“…This year was characterised by the lowest precipitation −236 mm, lower by 97 mm from the multiannual sum. The stress in potato production alters glycoalkaloid levels [55,56], and the expression of genes associated with glycoalkaloid synthesis are elevated by wounding or light [57]. According to Bejarano et al [55], a significant increase in TGA concentration was observed under drought stress conditions in most potato varieties (average However, one should note that, in 2004, the highest content was as much as 2.60 mg kg −1 FW.…”
Section: Tga Contentmentioning
confidence: 99%